2011
DOI: 10.3109/0886022x.2011.553301
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury in Adult Idiopathic Nephrotic Syndrome

Abstract: Objective: This study aims to investigate the epidemiology, clinical and histological features, and prognosis of acute kidney injury (AKI) according to RIFLE classification in adult patients with idiopathic nephrotic syndrome. Methods: In this retrospective study, 277 patients with idiopathic nephrotic syndrome were reviewed from June 2005 to June 2009. Results: Fifty-one (18%) patients entered RIFLE class Risk (AKI-R); 24 (9%) patients entered RIFLE class Injury (AKI-I); and 20 (7%) patients entered RIFLE cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 27 publications
5
22
0
Order By: Relevance
“…14 , 15 Risk factors for ARF include severe hypoalbuminemia, older age (in adults), and infection (in children). 16 The incidence of ARF in this study was 1.22%, which is consonant with the rates of 0.8% to 5% noted in previous reports. 17 Another very rare complication, acute hypertensive encephalopathy, is a transient neurologic dysfunction induced by marked increases in blood pressure during a moderate to severe nephrotic state.…”
Section: Discussionsupporting
confidence: 92%
“…14 , 15 Risk factors for ARF include severe hypoalbuminemia, older age (in adults), and infection (in children). 16 The incidence of ARF in this study was 1.22%, which is consonant with the rates of 0.8% to 5% noted in previous reports. 17 Another very rare complication, acute hypertensive encephalopathy, is a transient neurologic dysfunction induced by marked increases in blood pressure during a moderate to severe nephrotic state.…”
Section: Discussionsupporting
confidence: 92%
“…A recent retrospective study (1) showed that AKI, defined according to the newly developed RIFLE international consensus classification criteria (4), was observed in 95 of 277 adult idiopathic NS cases, consistent with the observations of previous studies. Immunotherapy takes some weeks to reduce proteinuria and increase the glomerular filtration rate (GFR), thereby alleviating fluid excess and hypoxia.…”
Section: Discussionsupporting
confidence: 85%
“…In previous studies, Waldman et al [5] and Chen et al [6] showed that MCD patients with AKI were more likely to be older and have a lower serum albumin level. Age and the albumin level were the confounding factors that affect coagulation and thromboembolism.…”
Section: Introductionmentioning
confidence: 99%